TRADISI PEMBACAAN SURAH AL-WAQI’AH Studi Living Qur’an DI PONDOK PESANTREN AL-TANWIRIYYAH AL-ARFIYYAH NGETOS: Studi Living Qur’an DI PONDOK PESANTREN AL-TANWIRIYYAH AL-ARFIYYAH NGETOS NGANJUK - Najib, M. Miftahun (LPPM IAI Hasanuddin Pare-Kediri, 2023)
This research discussed the tradition of reciting Surah al-Waqi'ah conducted at Islamic Boarding School (R; pesantren) of al-Tanwiriyyah al-Arfiyyah Mojoduwur, Ngetos, Nganjuk. In this pesantren, all students are required to follow this routine tradition so that they get used to practising it in their daily lives. The purpose of this study is to reveal the objective, expressive and documentary meanings of this Waqi'ah recitation activity by using apraching of Living Qur'an studies. While the method used is a qualitative method with a social approach and descriptive presentation. This study resulted in the following conclusions; the objective meaning of the recitation of surat al-Waqi'ah is a diploma about the Waqi'ah recitation model carried out by Sultanul 'Auliya' Sheikh 'Abdul Qadir al-Jailani. While the expressive meaning of reading Surah al-Waqi'ah is that it can provide relief in times of difficulty, ease in solving problems, smoothness in seeking knowledge and ease in obtaining sustenance. The documentary meaning is that it can make students become disciplined people in religion, and increase faith in depending on Allah SWT.